Effect of Heat Treatment on Phytochemical Content and Antioxidant Activity of Fresh and Boiled Capsicum Annum Variety Kulai - NAJIHAH, NURUL; Muhammad, Norhayati (Enhanced Knowledge in Sciences and Technology, 2023)
Capsicum annuum L var. Kulai belongs to the Solanaceae family or better known as red chili. Fresh Chili is a vegetable that has a high antioxidant content but the antioxidant content in chili is reduced after heat treatment boiling which uses three different temperatures which are 60,80 and 100℃.The objectives of this research were to determine the total phenolic content (TPC), total flavonoid content (TFC) and DPPH radical scavenging activities of fresh and boiled C.annum L var.Kulai. Total Phenolic content and total flavonoid were evaluated using Folin -Ciocaltue reagent and aluminium chloride, respectively. The antioxidant activity was tested using 2,2-diphenyl-1-picryhydrazyl (DPPH) free radical scavenging assay. The results showed chili was boiled with 60 the highest total phenolic content of 94.054±0.061 mg GAE/g.  Besides that, chili was boiled with 60  also demonstrated the highest total flavonoid content and capsaicin content (63.837±0.131 QE/g and 150.390±1.533µg/g). C.annum L var Kulai at 60  recorded the highest % inhibition of 75.446%. However, fresh C.annum L var Kulai reported the highest TPC ,TFC and DPPH  from  heat treatment. Thus, it can conclude the heat treatment can reduce phytochemical compound and antioxidant activities in C.annum L var Kulai